Kesadaran Hukum Masyarakat Dalam Pelaksanaan Protokol Kesehatan Covid-19 - Muhamad Arfiyanto (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
Legal awareness is a condition where there are no conflicts of life in society. The community is in a state of balance, harmony and harmony in carrying out legal awareness. Many people lack legal awareness, for example in carrying out the Covid-19 health protocol when Large-Scale Social Restrictions (PSBB) are being carried out, there are still many people carrying out activities in public places that cause crowds not to keep their distance from each other, not wearing masks, and not always washing. hands lead to an increase in the number of Covid-19 cases. The aim is to find out the legal awareness of the community in implementing the Covid-19 protocol. This study uses a sociological juridical approach, which emphasizes research that aims to obtain legal knowledge empirically by going directly to the object. The results of this study, namely the lack of public legal awareness in the application of Large-Scale Social Restrictions (PSBB) triggers the ineffectiveness of government efforts to reduce the spread of Covid-19 in Indonesia.